DAMPAK KEBIJAKAN PEMERINTAH TENTANG SURAT EDARAN MENTERI PENDAYAGUNAAN APARATUR NEGARA DAN REFORMASI BIROKRASI NO 11 TAHUN 2014 TERHADAP MINAT BERKARIR DI BIDANG PERHOTELAN (Studi Kasus Mahasiswa Sekolah Tinggi Pariwisata Bali Internasional) - Ni Wayan Rena Mariani; Firlie Lanovia; Ni Komang Nariani; Nyoman Surya Wijaya; I Gusti Made Sukaarnawa (Institut Pariwisata dan Bisnis Internasional, 2015)
Policy of Government through Circular Minister of Administrative and Beraucratic Reform No. 11/2014 contains a ban on the whole range of civil state apparatus governance activities outside government agencies apply from Desember 1, 2014 alarmed hospitality businesses. Chariman of the Indonesian Hotel and Restaurant Association (IHRA) Wiryanti Sukamdani recognize this policy has had an impact on revenue of the hotel. If the hotel continued to decline, will possibly be happen of Termination of Employment.Employment synonymous with career opportunities. Orientation of hospitality students can be ascertained by majoriy is looking for a job after graduation, when the availiability of jobs in particular field is getting narrower, it is fear will affect the interest of students for career in th hospitality field. This research aims to examine and analyze empirically the effect of the impact of government policy through Circular Letter of Minister of PAN and RB no. 11 of 2014 on the prohibiton of carrying out activities for government personnel outside the government agencies against the interest of student majoring in hospitality School of Tourism Bali International for career in the field of hospitality.Result of the research concludes that impact of government policy on Circular Letter of Minister of PAN and RB no 11 of 2014 negatively affect the interests of student for career in the hospitality field is not proven true, in this case indicates that the interests of students the School of Tourism Bali International (STPBI) for career in the hospitality affected bu the impact of government policies is significantly positive